PERTANGGUNGJAWABAN NASABAH YANG TIDAK MEMBAYAR HUTANG DI PLATFORM PINJAMAN ONLINE ILLEGAL PERSPEKTIF WAHBAH ZUHAILI (Studi Kasus Kota Medan) - Ulfianti (P2WP MUI Sumatera Utara, 2023)
Abstract Online loans are a platform that is currently in great demand because it provides unsecured loans. However, the problem is that many people are trapped in illegal online loans with very high interest rates and the spread of data that disturbs tranquility. The Indonesian state itself ordered not to pay debts that were in illegal loans. This is contrary to the principle of debt liability according to Wahbah Az Zuhaili. In this study, the author formulated a study, namely What are the factors of customers indebtedness on illegal online loan platforms in Medan City? What are the arrangements regarding debt repayment on illegal online loan platforms in Indonesia? How is the accountability of customers who do not pay debts on illegal online lending platforms from the perspective of Wahbah Az-Zuhaili? This research uses a type of empirical legal research with a case approach and a concept approach. The results showed that the factor of customers owing debt on illegal online loan platforms in Medan City is due to the ease of selecting illegal loans themselves, due to urgent economic needs, as well as very minimal financial literacy, making illegal loan customers always trapped in the entanglement of illegal loans which are famous for data leakage and tightening during billing. Arrangements regarding debt repayment on illegal online loan platforms in Indonesia are actually regulated in the Civil Code. Illegal pinjol is a loan that does not register with the state and does not comply with regulations. The principle is a halal business according to the Criminal Code itself refers to business entities that are registered and comply with government regulations. Meanwhile, illegal loans do not do this so that according to the civil law order in Indonesia, not paying debts in illegal loans is not a violation of the law, but it is not problematic if it is done because illegal loans are a form of legal entity that does not comply with government regulations and is not officially registered, causing this business is not a business of a halal form. In Wahbah Az-Zuhaili's view, customers should be responsible for debt repayment in illegal online loans because every debt in principal must be repaid. So according to Wahbah Az-Zuhaili, customers who do not pay their debts in illegal loans are customers who are not responsible for their debts and these actions are considered to violate the provisions of the law on qard. Even though the platform is illegal, it still does not abort the obligation to pay debts. Keywords: Illegal Online Loans, Liability, Wahbah Az Zuhaili.